0364 GOOD Sleep Care: Geospatial Optimization of Distant Sleep Care in the VA. (25th May 2022) - Atwood, Charles; Smith, Conor; Totten, Annette; Boudreau, Eilis; Sarmiento, Kathleen; Hahn, Zachary; Folmer, Robert; Tock, Jamie; Hotchkiss, John
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is very prevalent in the Veterans Administrations (VA) clinical population, affecting about 24% of Veterans. Sleep medicine services in VA suffers from uneven distribution, which especially affects Veterans in rural populations, where care is often not available except by long distance travel. Travel burden is increasingly recognized as a burden on Veteran care that can be ameliorated by telemedicine. Little is known about travel burden and few attempts have been made to quantify it. We have attempted to quantify travel burden for rural Veterans using data from VA's Office of Rural Health supported Enterprise Wide Initiative for Telesleep Medicine. In this project we focus on travel from a Veteran's home to a facility-based sleep clinic visit (traditional face-face visit) vs. how much travel would be avoided if visits were performed using video-based telemedicine with the Veteran at his/her residence. Methods: Purpose built geocoding software (validated in prior studies) was used to quantify the driving distance from the Veterans home zipcode to the zipcode of the facility where the visits would were performed. The data were taken from the VA's national corporate data warehouse (CDW). Over 4 million sleep encounters were coded. CPT4 codes were used to define the clinic visit encounters from 2016 through 2020. We set the travel range where telemedicine is reasonable based on distance at greater than 40 miles from the VA medical center which is how VA currently defines "distant travel". Results: No. of Encounters (thous) 2016, 557; 2017, 623; 2018, 678; 2019, 667; 2020, 420Miles ObsTravel (mil) 2016, 38; 2017, 42; 2018, 45; 2019, 43; 2020, 27 Miles Travel if telemed used (mil) 2016, 25; 2017, 27; 2018, 29; 2019, 27: 2020, 17Difference (mil miles) 2016, 13; 2017, 15; 2018, 16; 2019, 16 2020, 10Between 10 and 16 million miles could be saved each year for sleep medicine visits if all travel > 40 miles was converted to video home visits. Conclusion: Travel burden in this analysis, defined by miles driven to and from a sleep medicine encounter, could be dramatically reduced if telemedicine visits were used for sleep apnea evaluation and management. This reduction in travel equates to a reduction in automobile related use-costs, lower carbon footprint, fewer automobile crashes with injury and death. Assuming that clinical effectiveness of home telemedicine is comparable to traditional visits, these data support the vigorous adoption of telemedicine for sleep medicine services. Support (If Any): VA Office of Rural Health; Measurement QUERI, San Francisco VA Medical